2006
DOI: 10.1007/s10695-006-9106-5
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of protease, amylase and lipase in the alimentary tract of hybrid Juvenile tilapia (Oreochromis niloticus × Oreochromis aureus)

Abstract: Juvenile tilapias (Oreochromis niloticus · O. aureus), with average body weights of groups I, II and III of 55.14, 122.82, and 225.68 g respectively were used to study changes in the activity of protease, amylase, and lipase in different organs and sections of the alimentary tract. Additionally, tract containing digesta, which is closer to physiological conditions, may help reveal the mechanisms of whole chemical digestion process. Another group of tilapias (mean body weight of 111.81 ± 0.14 g) was used to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…A great number of studies have been oriented to quantification of digestive proteases in the gut of different fish species (Drewe et al 2004;Lundstedt et al 2004;Chakrabarti et al 2006;Jun-sheng et al 2006). Most of those studies express such activities in relation to mg of soluble protein (specific activity) or mg of tissue.…”
Section: Discussionmentioning
confidence: 99%
“…A great number of studies have been oriented to quantification of digestive proteases in the gut of different fish species (Drewe et al 2004;Lundstedt et al 2004;Chakrabarti et al 2006;Jun-sheng et al 2006). Most of those studies express such activities in relation to mg of soluble protein (specific activity) or mg of tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Activity without sodium taurocholate was considered as 100% Optimal pH for the lipase activity in S. aurata was found to be close to 9, being in agreement with the optimal pH reported for other intestinal enzymes in this species (Munilla-Moran and Saborido-Rey 1996a, b). Similar values have been described for lipases in other fish species like the rainbow trout (Oncorhynchus mykiss), cod (Gadus morhua), red sea bream (Pagrus major), Pacific blue tuna (Thunnus orientalis), grey mullet (Liza parsia), Chinook salmon (Oncorhynchus tshawytscha) and hoki (Macruronus novaezelandiae), or carnivorous teleost fish of Tibet (Glyptosternum maculatum) (Metin and Akpinar 2000;Tocher and Sargent 1984;Gjellesvik et al 1989;Iijima et al 1998;Matus de la Parra et al 2007;Islam et al 2008;Kurtovic et al 2010;Xiong et al 2010, respectively), while maximum activity at a more neutral pH has been reported in species like Cyprinion macrostomus or the tilapia (Taniguchi et al 2001;Degerli and Akpinar 2002;Jun-Sheng et al 2006). The lipase activity was highly stable at pH 7-8, this being in agreement with the pH range found for many fish intestinal digestive enzymes (Iijima et al 1997;Ugolev andKuz 0 mina 1993, in Kuzmina andUshakova 2007), as well to the normal pH values measured in the intestine of this species (Deguara et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of digestive lipases has been carried out in different fish species like Pagrus major (Iijima et al 1998), Pseudoplatystoma corruscans (Lundstedt et al 2004), Oreochromis spp. (Jun-Sheng et al 2006), Thunnus orintalis (Matus de la Parra et al 2007), Oncorhynchus tshawytscha and Macruronus novaezelandiae (Kurtovic et al 2010), or Glyptosternum maculatum (Xiong et al 2010. Other aspects, like its changes with larval development (Izquierdo and Henderson 1998;Cahu et al 2000), effect of diet on lipase activity (Debnath et al 2007;Hansen et al 2008;Chatzifotis et al 2008), or the effect of supplementary lipase on growth and body composition (Samuelsen et al 2001) have been also assessed.…”
Section: Introductionmentioning
confidence: 99%
“…The most important enzymes for digestion are peptidases (CHAKRABARTI et al 1995, CASTILLO-YÁÑEZ et al 2006, JUN-SHENG et al 2006, KLOMKLAO et al 2007, BOUGATEF et al 2010, the lipases (NATALIA et al 2004, JUN-SHENG et al 2006 and enzymes that hydrolyze carbohydrates such as amylases, maltases, chitinases and glucosidases (KUZ'MINA et al 1996, PAPOUTSOGLOU & LYNDON 2006). An important aspect of this is the distribution of enzymes in the organs involved in the biosynthesis of digestive Influence of season, environment and feeding habits on the enzymatic activity of peptidase and ␤ ␤ ␤ ␤ ␤-glucosidase in the gastrointestinal tract of two Siluriformes fishes (Teleostei) activities (BUDDINGTON & DIAMOND 1986, BAIRAGI et al 2002, BOUGATEF et al 2010, which can change among species, seasons and environmental conditions.…”
mentioning
confidence: 99%